2
$\begingroup$

Let $$K=\{x=(x(n))_n\in l_2(\mathbb{N}):\|x\|_2\le 1\ \text{ and } x(n)\ge 0 \text{ for all } n\in \mathbb{N} \}$$ and define $T:K\to c_0$ by $T(x)=(1-\|x\|_2,x(1),x(2),\ldots)$. Prove :

(1) $T$ is self map on $K$ and $\|Tx-Ty\|_2\le \sqrt{2} \|x-y\|_2$

(2) $T $ does not have fixed points in $K$

my attempt

for (2):

suppose $T$ have fixed point i.e., $Tx=x$

then $(1-\|x\|_2, x(1),x(2),\ldots)=(x(1),x(2),\ldots)$

then $x(1)=1-\|x\|_2, x(2)=x(1), x(3)=x(2),\ldots$

$$\therefore \|x\|_2 =\left(\sum ^n_{n=\infty} |x(n)|^2\right)^\frac{1}{2} = \left(\sum ^n_{n=\infty} (1-\|x\|_2)^2\right)^\frac{1}{2}$$

but how to prove this $x$ is not in $K$?

how to prove (1)

$\endgroup$
  • $\begingroup$ It seems that your calculation does not match the definition of $T$. $\endgroup$ – Song Mar 24 at 8:01
  • $\begingroup$ @Song..now i edited correctly thank you $\endgroup$ – Inverse Problem Mar 24 at 8:13
2
$\begingroup$

For $(2)$ you got that if $Tx = x$ then $$x = (1-\|x\|_2, 1-\|x\|_2, \ldots)$$

so $$+\infty > \|x\|_2^2 = \sum_{n=1}^\infty (1-\|x\|_2)^2$$ The only way this series converges is if $1-\|x\|_2 = 0$, or $\|x\|_2 = 1$, so $x = (1,1,1\ldots )$. But then clearly $\|x\|_2 = +\infty$ and not $1$ so this is a contradiction.


To show that $T$ is actually a map $K \to K$, take $x \in K$ and we claim that $Tx \in K$ as well.

Since $\|x\|_2 \le 1$ we have $1-\|x\|_2 \ge 0$ so

\begin{align} \|Tx\|_2^2 &= (1-\|x\|_2)^2 + \sum_{n=1}^\infty |x_n|^2 \\ &= (1-\|x\|_2)^2 + \|x\|_2^2 \\ &\le (1-\|x\|_2)^2 + 2(1-\|x\|_2)\|x\|_2 + \|x\|_2^2 \\ &= (1-\|x\|_2+\|x\|_2)^2 \\ &= 1 \end{align}

which means $\|Tx\|_2 \le 1$.

Also clearly all coordinates of $$Tx = (1-\|x\|_2, x_1, x_2, \ldots)$$ are nonnegative since $x_n \ge 0, \forall n \in \mathbb{N}$ and $1-\|x\|_2 \ge 0$.

Therefore $Tx \in K$.

$\endgroup$
  • $\begingroup$ @mechanodroid...thank you so much but i have doubt with how to show $T$ is self map in question (1) $\endgroup$ – Inverse Problem Mar 24 at 10:27
  • $\begingroup$ @InverseProblem Have a look. $\endgroup$ – mechanodroid Mar 24 at 10:42
  • $\begingroup$ @mechanodroid......thank you so much ......for your help $\endgroup$ – Inverse Problem Mar 24 at 12:51
  • $\begingroup$ @mechanodroid...can you give some hint this question please...math.stackexchange.com/questions/3159556/… $\endgroup$ – Inverse Problem Mar 24 at 13:09
  • $\begingroup$ @InverseProblem I have added an answer, can you explain what exactly is $T$ in the definition of $T_n$? $\endgroup$ – mechanodroid Mar 24 at 15:48
2
$\begingroup$

You're on the right track.

As you said - $||x||_2 =(\sum ^\infty_{n=1} |1-||x|||_2|^2)^\frac{1}{2}$

There is only one possible way for this sum to converge - if and only if $||x||_2=1$. But in this case, we also get $||x||_2=0$ - a contradiction.

About (1) - let's try evaluating the required norm:

$||Tx-Ty||_2=||(1-||x||_2,x(1),x(2),...)-(1-||y||_2,y(1),y(2),...)||_2\\=||(||y||_2-||x||_2,x(1)-y(1),x(2)-y(2),...)||_2\\=(|||y||_2-||x||_2|^2+\sum ^\infty_{n=2} |x(n)-y(n)|^2)^\frac{1}{2}\\=(|||y||_2-||x||_2|^2-|x(1)-y(1)|^2+\sum ^\infty_{n=1} |x(n)-y(n)|^2)^\frac{1}{2}\\\leq(||x-y||_2^2-|x(1)-y(1)|^2+||x-y||_2^2)^\frac{1}{2}\\=(2||x-y||_2^2-|x(1)-y(1)|^2)^\frac{1}{2}\\ \leq \sqrt2||x-y||_2$

(Every $\leq$ sign is due to triangle inequality)

$\endgroup$
  • $\begingroup$ ..can you tell me how to prove self map $\endgroup$ – Inverse Problem Mar 24 at 9:09
  • $\begingroup$ I'm not familiar with that term, what does it mean? $\endgroup$ – GSofer Mar 24 at 9:11
  • $\begingroup$ it means that we have to prove $T$ map from $K$ to $K$ $\endgroup$ – Inverse Problem Mar 24 at 9:13
1
$\begingroup$

It seems to me one may not need the assumption $x(n)\geq 0$. In fact, if $Tx=x$, then $\|Tx\|^2=\|x\|^2$ which says $(1-\|x\|)^2+x(1)^2+x(2)^2...=x(1)^2+x(2)^2+...$, so we see $\|x\|=1$. Then $x(1)=0$. Let $n$ be the first integer with $x(n)\neq 0$, there exists such $n$ since $\|x\|=1$. So $x(n-1)=0$, but the $n$-th component in $Tx$ is $x(n-1)=0$, contradicts $Tx=x$ and $x(n)\neq 0$.

Part 1: $\|Tx-Ty\|^2=[(1-\|x\|)-(1-\|y\|)]^2+[x(1)-y(1)]^2+...=(\|x\|-\|y\|)^2+\|x-y\|^2\leq \|x-y\|^2+\|x-y\|^2=2\|x-y\|^2$ .

$\endgroup$
  • $\begingroup$ Ding....can you tell how to prove this is self map $\endgroup$ – Inverse Problem Mar 24 at 9:08
  • $\begingroup$ From $\|x\|\leq 1$, the condition $x(n)\geq 0$ is preserved by $T$. Next, $\|Tx\|^2=(1-\|x\|)^2+\|x|^2\leq 1$, here one uses the elementary inequality $(1-a)^2+a^2\leq 1$ when $0\leq a\leq 1$, which can be checked by finding the maximum of $(1-a)^2+a^2$ on $[0, 1]$. $\endgroup$ – Yu Ding Mar 24 at 9:17
  • $\begingroup$ what is this mean when u want to prove a map is self map it means we have to prove that map itself to a set\ $\endgroup$ – Inverse Problem Mar 24 at 9:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.